Pemakaian Anggah-Ungguhing Basa Bali pada Buku Ajar Bahasa Bali di SMA: Kajian Sosiolinguistik - Suryati, Ni Made; Mulyawati R., Tjok. Istri Agung (Humanis; Vol 26 No 4 (2022), 2022)
The article's objectives were 1) to examine the usage of Balinese language in Balinese language textbooks in senior high schools at the discourse, sentences, and word levels. This is a qualitative research study. The written material comes from a textbook titled Kusuma Sastra for Class XI. Data were obtained using the listening method, which was assisted by note-taking techniques, and analyzed using distributional and distributional methods, which were supported by substitution techniques. Informal approaches are used to provide data analysis, which is aided by inductive and deductive processes. The article's research results: the use of Balinese anggah-ungguhing basa in a textbook titled Kusuma Sastra: (1) at the discourse level: alus, kepara, and mixed), (2) at the sentence level: alus singgih, alus sor, kepara, kasar hormat), and (3) at the word level: alus singgih, alus sor, mider, madia, andap, and kasar).